Histone Deacetylase Inhibitors Modulate the Transcriptional Regulation of Guanylyl Cyclase/Natriuretic Peptide Receptor-A Gene: INTERACTIVE ROLES OF MODIFIED HISTONES, HISTONE ACETYLTRANSFERASE, p300, AND Sp1 - Kumar, Prerna (American Society for Biochemistry and Molecular Biology, 2014)
Atrial natriuretic peptide (ANP) binds guanylyl cyclase-A/natriuretic peptide receptor-A (GC-A/NPRA) and produces the intracellular second messenger, cGMP, which regulates cardiovascular homeostasis. We sought to determine the function of histone deacetylases (HDACs) in regulating Npr1 (coding for GC-A/NPRA) gene transcription, using primary mouse mesangial cells treated with class-specific HDAC inhibitors (HDACi). Trichostatin A, a pan inhibitor, and mocetinostat (MGCD0103), a class I HDAC inhibitor, significantly enhanced Npr1 promoter activity (by 8- and 10-fold, respectively), mRNA levels (4- and 5.3-fold, respectively), and NPRA protein (2.7- and 3.5-fold, respectively). However, MC1568 (class II HDAC inhibitor) had no discernible effect. Overexpression of HDAC1 and HDAC2 significantly attenuated Npr1 promoter activity, whereas HDAC3 and HDAC8 had no effect. HDACi-treated cultured cells in vitro and intact animals in vivo showed significantly reduced binding of HDAC1 and -2 and increased accumulation of acetylated H3-K9/14 and H4-K12 at the Npr1 promoter. Deletional analyses of the Npr1 promoter along with ectopic overexpression and inhibition of Sp1 confirmed that HDACi-induced Npr1 gene transcription is accomplished by Sp1 activation. Furthermore, HDACi attenuated the interaction of Sp1 with HDAC1/2 and promoted Sp1 association with p300 and p300/cAMP-binding protein-associated factor; it also promoted the recruitment of p300 and p300/cAMP-binding protein-associated factor to the Npr1 promoter. Our results demonstrate that trichostatin A and MGCD0103 enhanced Npr1 gene expression through inhibition of HDAC1/2 and increased both acetylation of histones (H3-K9/14, H4-K12) and Sp1 by p300, and their recruitment to Npr1 promoter. Our findings define a novel epigenetic regulatory mechanism that governs Npr1 gene transcription.